PERLINDUNGAN KONSUMEN DI INDONESIA - -, Dahlia (Universitas Slamet Riyadi, 2010)
AbstractLaw No. 8 of 1999 on Consumer Protection must be upheld in business and trade relations in general for the creation of a justice. Criminal provisions should be placed as Primum remedium About Consumer Protection Act so that it really works with its criminal sanctions as special and general prevention of corporate crime. Key words : Consumer protection